Interculturality in Bilingual Public Education in Bogotá D.C. - Lozano Ñustes , Marisol (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This article is a reflection on the intercultural phenomenon in foreign language teaching classrooms. Initially, the cultural diversity of the classrooms is contextualized, and this question is posed: How is cultural identity being addressed in the foreign language teaching classrooms of public bilingual educational institutions in Bogotá? Then, concepts such as cultural identity, among others, are defined; Some public policies for bilingual education in public institutions in Bogotá are mentioned, and some studies are cited on the relationship between teaching/learning of a foreign language and interculturality. Finally, a reflection on the question posed is exposed.